Phospholipase C-related catalytically inactive protein regulates lipopolysaccharide-induced hypothalamic inflammation-mediated anorexia in mice. (December 2019) - Yamawaki, Yosuke; Shirawachi, Satomi; Mizokami, Akiko; Nozaki, Kanako; Ito, Hikaru; Asano, Satoshi; Oue, Kana; Aizawa, Hidenori; Yamawaki, Shigeto; Hirata, Masato; Kanematsu, Takashi
Abstract: Peripheral lipopolysaccharide (LPS) injection induces systemic inflammation through the activation of the inhibitor of nuclear factor kappa B (NF-κB) kinase (IKK)/NF-κB signaling pathway, which promotes brain dysfunction resulting in conditions including anorexia. LPS-mediated reduction of food intake is associated with activation of NF-κB signaling and phosphorylation of the transcription factor signal transducer and activator of transcription 3 (STAT3) in the hypothalamus. We recently reported phospholipase C-related catalytically inactive protein (PRIP) as a new negative regulator of phosphatidylinositol 3-kinase/AKT signaling. AKT regulates the IKK/NF-κB signaling pathway; therefore, this study aimed to investigate the role of PRIP/AKT signaling in LPS-mediated neuroinflammation-induced anorexia. PRIP gene ( Prip1 and Prip2 ) knockout ( Prip -KO) mice intraperitoneally (ip) administered with LPS exhibited increased anorexia responses compared with wild-type (WT) controls. Although few differences were observed between WT and Prip -KO mice in LPS-elicited plasma pro-inflammatory cytokine elevation, hypothalamic pro-inflammatory cytokines were significantly upregulated in Prip -KO rather than WT mice. Hypothalamic AKT and IKK phosphorylation and IκB degradation were significantly increased in Prip -KO rather than WT mice, indicating further promotion of AKT-mediated NF-κB signaling. Consistently, hypothalamic STAT3 was further phosphorylated in Prip -KO rather than WT mice. Furthermore, suppressor of cytokine signaling 3 ( Socs3 ), a negative feedback regulator for STAT3 signaling, and cyclooxogenase-2 ( Cox2 ), a candidate molecule in LPS-induced anorexigenic responses, were upregulated in the hypothalamus in Prip -KO rather than WT mice. Pro-inflammatory cytokines were upregulated in hypothalamic microglia isolated from Prip -KO rather than WT mice. Together, these findings indicate that PRIP negatively regulates LPS-induced anorexia caused by pro-inflammatory cytokine expression in the hypothalamus, which is mediated by AKT-activated NF-κB signaling. Importantly, hypothalamic microglia participate in this PRIP-mediated process. Elucidation of PRIP-mediated neuroinflammatory responses may provide novel insights into the pathophysiology of many brain dysfunctions. Highlights: Prip -KO mice show susceptibility to LPS-induced anorexia. PRIP deficiency enhances LPS-induced hypothalamic inflammatory cytokine expression. PRIP deficiency enhances hypothalamic AKT/NF-κB/STAT3 signaling after LPS treatment. PRIP deficiency enhances inflammatory responses in hypothalamic microglia. PRIP negatively regulates the progression of LPS-induced anorexia.